A single-item self-rated health measure correlates with objective health status in the elderly: a survey in suburban Beijing - Qinqin eMeng; Zheng eXie; Tuohong eZhang (Frontiers Media S.A., 2014)
Introduction The measurement of health status of the elderly remains one important topic. Self-rated health status (SRH) is considered to be a simple indicator to measure the health status of the old population. But some researchers still take a skeptical view about its reliability. This study aims to investigate the association between self-rated health indicator and health status of the elderly and discuss its subsequent public health implications. Methods In a total 1096 people who were 60 years of age or older from 1784 households from a suburban area of Beijing were interviewed using multistage stratified cluster sampling. SRH was measured by a single question please choose one point in this 0-100 scale which can best represent your health today?. The disease status and physical functional status were also obtained. A multiple linear regression was conducted to test the associate between SRH and individual's disease/functional status. Results The average of SRH scores of the elderly was 72.49±15.64 (on a 1 to 100 scale). The SRH scores declined not only with the severity of self-reported mental/disease status, but also with the decrease of physical functional status. Multiple linear regression showed that after adjustment for other variables, two-week sickness, chronic diseases, hospitalization, and ability of self-care (washing and dressing) were able to explain 35% of the variation in SRH among the elderly. Among them, disease status and self-care ability were the most powerful predictor of SRH. After adjusting other variables, physical functional status could explain only 5% of the variation in SRH. Conclusion SRH reflects the disease/functional health status of the elderly. It is an easy-to-implement variable and it can reduce both recall bias and investigator bias, thus being widely used in health surveys. It is a cost-effective means of measuring the health status. However, the comparability of SRH in different populations should be studied in future